Coccygeal fistula. Pilonidal cyst: Analysis of 45 cases. Semi-closed procedure - Praderi, Luis A.; Pérez Tambasco, Ricardo; Praderi Gambardella, Luis (Cirugía del Uruguay, 1986)
We have discussed the problem of the coccygeal fislula, surgical indications, its extended postoperative morbility and frequent recidivation. Methods employed have been classified into open and close and main variations of same and we propose a modificatlon of Mac Fee's method. We have applied said variation in 24 cases reducing the postoperative period for recivery and recidivation.